A study of the effect of thinning on the yield, composition, palatability and digestibility of marrow-stem kale : a thesis presented ... for the degree of M. Ag. Sc. in the University of New Zealand, Massey Agricultural College. - Frame, John (Massey University, 1957)
Due to climate and other natural advantages, the livestock industry in New Zealand is based upon a pastoral economy. The large-scale use of grassland and its products, hay and silage, for feeding the livestock, gives the industry its low-cost production structure. However, one of the problems associated with this dependency upon grassland is that of fitting seasonal production of pasture to stock requirements. [From Introduction]
Best copy available due to the condition of the original copy.
Keywords: Kale